2020
DOI: 10.1111/tid.13332
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of noncirrhotic hyperammonemia syndrome after kidney transplantation from putative Ureaplasma infection

Abstract: Noncirrhotic hyperammonemia (NCH) is a rare but often fatal complication of solid organ transplantation. We present a case wherein an infectious cause of NCH was suspected following kidney transplantation (KT) and the patient was promptly started on empirical antibiotic treatment which proved to be lifesaving. A 56-year

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In the postlung transplant setting, these organisms are known to cause mediastinitis, surgical site infection pericarditis, empyema, bronchial anastomosis complications, and have been associated with fatal cases of hyperammonemia syndrome, which is far more frequent in lung recipients [ 32 , 33 ▪▪ , 34 ].…”
Section: Mollicutesmentioning
confidence: 99%
“…In the postlung transplant setting, these organisms are known to cause mediastinitis, surgical site infection pericarditis, empyema, bronchial anastomosis complications, and have been associated with fatal cases of hyperammonemia syndrome, which is far more frequent in lung recipients [ 32 , 33 ▪▪ , 34 ].…”
Section: Mollicutesmentioning
confidence: 99%
“…Three studies 29,31,34 reported using azithromycin, levofloxacin, and doxycycline to manage hyperammonemia syndrome in these patients. Based on 14 studies, 13,16,23–35 the median length of treatment for HS patients was 21 (range: 2–120) days. For those patients who were started on initial treatment with β‐lactam antibiotics ( n = 2), symptoms and ammonia levels of HS did not improve 23,28 .…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart shows the search process and study selection (Figure 1). We identified 18 relevant articles, which met the inclusion criteria for qualitative synthesis, of which 13 were case reports 13,[23][24][25][26][27][28][29][30][31][32][33][34] and 2 were case series. 16,35 Only 3 were included for meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…We compared these presentations to nonlung SOT recipients (isolated liver transplants were excluded given the association of hyperammonemia syndrome with liver failure) as shown in Table 2. In nonlung SOT, there were 12 cases of hyperammonemia syndrome, 9 (75%) in kidney recipients, 2 (16.7%) in heart recipients, and 1 (8.3%) a dual kidney–liver recipient [2,26,53–62]. Key differences in the nonlung SOT population compared with the lung population include higher initial (472.5 vs. 206, P = 0.064) and peak (555.5 vs. 339.5, P = 0.656) serum ammonia levels, and a lower mortality rate of 25% ( n = 3 of 12, P = 0.056).…”
Section: Clinical Presentationmentioning
confidence: 97%
“…We compared these presentations to nonlung SOT recipients (isolated liver transplants were excluded given the association of hyperammonemia syndrome with liver failure) as shown in Table 2. In nonlung SOT, there were 12 cases of hyperammonemia syndrome, 9 (75%) in kidney recipients, 2 (16.7%) in heart recipients, and 1 (8.3%) a dual kidney-liver recipient [2, 26,[53][54][55][56][57][58][59][60][61][62].…”
Section: Clinical Presentationmentioning
confidence: 99%